2014
DOI: 10.1149/2.0191412jes
|View full text |Cite
|
Sign up to set email alerts
|

The Composition-Dependent Color Evolution of Anodic Electrodeposited Cerium Oxide Thin Film

Abstract: Cerium oxide thin films with various colors were deposited onto 316L stainless steel using anodic electrodeposition approach. The correlation between color, composition and deposition time has been established. Results show that the film color evolves from golden yellow (1.5 h), purple (3 h), blue (5 h), gray-green (7 h) and turns back to yellow (12 h) again, and all these colored films are stable in the ambient conditions. The film color is related to both the contents of Ce(III) and hydroxide species in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…The ceria film mainly consists of cerium and oxygen, which mainly exist as CeO 2 , Ce 2 O 3 and their hydrates such as Ce(OH) 4 , Ce(OH) 3 , 17 while the color of ceria film is related to their contents of Ce(III) and hydroxide species. 31 Table III clearly shows that Ce(III) content in all ceria films just falls into the dedicated range of yellow, 31 which may be the reason why all color of the anodic deposited CeO 2 layers in all solutions of different ethanol content is yellowish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceria film mainly consists of cerium and oxygen, which mainly exist as CeO 2 , Ce 2 O 3 and their hydrates such as Ce(OH) 4 , Ce(OH) 3 , 17 while the color of ceria film is related to their contents of Ce(III) and hydroxide species. 31 Table III clearly shows that Ce(III) content in all ceria films just falls into the dedicated range of yellow, 31 which may be the reason why all color of the anodic deposited CeO 2 layers in all solutions of different ethanol content is yellowish.…”
Section: Discussionmentioning
confidence: 99%
“…But there still has another possibility that ethanol can enhance the anodic deposition rate of ceria film by the effect of the simultaneously photo generated electrons (e − cb , reactions 5 and 13). Our previous works 20, [30][31] have electrodeposited CeO 2 films onto stainless steel substrates in the solutions without photo illumination, Journal of The Electrochemical Society, 162 (4) D166-D173 (2015) D167 and found that the addition of ethanol into the electroplating solution can decrease the surface tension of the solution and improve the wettability of the electrode, 31,32 and hence, results in a thinner but more compact film. 20 Whereas, ethanol can increase both the anodic polarization of film formation and the resistivity of bath solution, which as well leads to the thickness of the anodic deposited semiconductive ceria film decreasing with the increase of ethanol content.…”
mentioning
confidence: 99%